Analogical modeling and numerical simulation variant for distributed parameter processes, with applications in isotope separations, chemistry and thermo-energetics - Colosi, Tiberiu; Abrudean, Mihail; Unguresan, Mihaela-Ligia; Muresan, Vlad (2014 IEEE International Conference on Automation, Quality and Testing, Robotics, 2014)
This paper has an informal character. It is referring to distributed parameter processes whose analogical modeling and numerical simulation can be complex and laborious. In these cases, the following compromise can present a major interest: - the determination of some approximating solutions, relatively simple, but sufficiently close to the phenomena reality and on this base: - the elaboration of some analogical modeling and numerical simulation methods with a sufficiently unitary and systemized character based on partial differential equations and after case, with ordinary differential equations, too. In this case, it is proposed a) The analogical modeling through the method of the Matrix of Partial Derivatives of the State Vector (M pdx ); b) The numerical simulation through the (M pdx ) method associated with Taylor series and approximating solutions. This method was used with good results, in numerous examples, in isotope separations processes, thermo-energetics, chemistry, metallurgy, etc. [1-11].